Synthesis of the new derivative 1- Diphenylamine Enamine Ascorbic Acid, and study of its biological activity - Shollar, Mohammad Moatz Ghazi; Merza, Joumaa; Shereteh, Thanaa (Journal of natural sciences, life and applied sciences, 2021)
The new enamine [1- Diphenyl enamine ascorbic acid] has been prepared according to two methods: The first method was “The reaction between ascorbic acid and diphenylamine” has been done directly, however the yield was relatively low. The second method was “the reaction between ascorbic acid and diphenylamine” which has been carried out through three steps: In the first step, the hydroxyl groups in (5, 6) position have been protected using the acetone, in the second step, the hydroxyl groups in (2, 3) position have been protected using iodide methyl. The obtained compound (5, 6-dioxolan-2, 3-metoxy ascorbic acid) have been reacted with Diphenylamine to obtain the target molecule in the third step'' the structural determination has been confirmed using spectroscopy methods (FT-IR, 1H-NMR, 13C-NMR). The target compound gave very good biological activity against Gram-positive bacteria (Staphylococcus Aureus) and Gram-negative (Pseudomonas Aeruginosa) bacteria, with Gentamicin as a reference active compound.
Keywords: ascorbic acid; Diphenylamine; Enamine; Group protection; Biological activity